Synergistic Killing of Polymyxin B in Combination With the Antineoplastic Drug Mitotane Against Polymyxin-Susceptible and -Resistant Acinetobacter baumannii: A Metabolomic Study - Tran, Thien B.; Bergen, Phillip J.; Creek, Darren J.; Velkov, Tony; Li, Jian (Frontiers in Pharmacology, 2018)
Polymyxins are currently used as the last-resort antibiotics against multidrug-resistant Acinetobacter baumannii. As resistance to polymyxins emerges in A. baumannii with monotherapy, combination therapy is often the only remaining treatment option. A novel approach is to employ the combination of polymyxin B with non-antibiotic drugs. In the present study, we employed non-targeted metabolomics to investigate the synergistic mechanism of polymyxin B in combination with the antineoplastic drug mitotane against polymyxin-susceptible and -resistant A. baumannii. The metabolomes of four A. baumannii strains were analyzed following treatment with polymyxin B, mitotane and the combination. Polymyxin B monotherapy induced significant perturbation in glycerophospholipid metabolism and histidine degradation pathways in polymyxin-susceptible strains, and minimal perturbation in polymyxin-resistant strains. Mitotane monotherapy induced minimal perturbation in the polymyxin-susceptible strains but caused significant perturbation in glycerophospholipid metabolism and the pentose phosphate and histidine degradation pathways in the polymyxin-resistant strain which lacked LPS (FADDI-AB065). The polymyxin B - mitotane combination induced significant perturbation in all strains except the lipid A modified polymyxin-resistant FADDI-AB225 strain. For the polymyxin-susceptible strains, combination therapy significantly perturbed glycerophospholipid metabolism, the pentose phosphate pathway, citric acid cycle, pyrimidine ribonucleotide biogenesis, guanine ribonucleotide biogenesis, and the histidine degradation pathway. Against FADDI-AB065, the combination significantly perturbed only glycerophospholipid metabolism, the pentose phosphate pathway, citric acid cycle, and pyrimidine ribonucleotide biogenesis. Overall, these novel findings demonstrate that the disruption of the citric acid cycle and inhibition of nucleotide biogenesis are the key metabolic features associated with synergistic bacterial killing by the combination against polymyxin-susceptible and -resistant A. baumannii.